EU employment dynamics: The pandemic years and beyond - Stefan Jestl; Robert Stehrer (European Trade Union Institute (ETUI), 2021)
The economic shock induced by the pandemic has plunged European economies into a recession. Lockdowns and social distancing measures have affected economic life in a substantial way, with industries and population groups facing varying difficulties. This study explores potential future employment dynamics across European industries and employment groups for the period up to 2026 by drawing on past sectoral trends and the latest macroeconomic forecast results from the International Monetary Fund (IMF) and the European Commission. A scenario analysis is also carried out, taking into account the great uncertainty and risks that are related to the baseline forecasts. We consider four scenarios: The 'baseline scenario' presumes a strong economic recovery The 'negative scenario' reflects the possible emergence of one or more mutations which will spread more quickly and have a higher death rate. The 'worst-case scenario' presumes the emergence of new, more infectious virus variants. The 'more optimistic scenario' predicts an even stronger economic recovery in 2021 and 2022 compared to the baseline scenario [...]
Keywords: 330; employment; industry; forecast; EU countries; Erwerbstätigkeit; Branche; Prognose; EU-Staaten